2009
DOI: 10.1103/physrevlett.103.056404
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle Transformation during a Metal-Insulator Transition in Graphene

Abstract: Here we show, with simultaneous transport and photoemission measurements, that the graphene-terminated SiC(0001) surface undergoes a metal-insulator transition upon dosing with small amounts of atomic hydrogen. We find the room temperature resistance increases by about 4 orders of magnitude, a transition accompanied by anomalies in the momentum-resolved spectral function including a non-Fermi-liquid behavior and a breakdown of the quasiparticle picture. These effects are discussed in terms of a possible transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
195
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(218 citation statements)
references
References 32 publications
21
195
2
Order By: Relevance
“…Monte Carlo calculations in a lattice gauge theory framework predict the opening of a gap [31,54]. A gap has also been claimed in very recent angle-resolved photoemission spectroscopy (ARPES) measurements of epitaxial graphene upon dosing with small amounts of atomic hydrogen [55]. Disorder can give rise to various strong coupling phases [30,56,57] whose physical properties have only been partially explored [58].…”
Section: Opening a Gap In Graphene-excitonic Transitionmentioning
confidence: 99%
“…Monte Carlo calculations in a lattice gauge theory framework predict the opening of a gap [31,54]. A gap has also been claimed in very recent angle-resolved photoemission spectroscopy (ARPES) measurements of epitaxial graphene upon dosing with small amounts of atomic hydrogen [55]. Disorder can give rise to various strong coupling phases [30,56,57] whose physical properties have only been partially explored [58].…”
Section: Opening a Gap In Graphene-excitonic Transitionmentioning
confidence: 99%
“…Hydrogen adsorption on carbon based materials such as graphite and graphene is relevant to hydrogen storage, 9 band gap engineering, [10][11][12][13] and potentially as the first step in H 2 formation in the interstellar medium. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although there is enormous interest in H adsorption on carbonaceous surfaces, with graphene, graphite and polycyclic aromatic hydrocarbons (PAHs) being the most widely studied model systems, we still don't fully understand the seemingly simple process of how a single H atom adsorbs on the surface.…”
mentioning
confidence: 99%
“…Transport experiments have shown that the exposure of graphene to atomic hydrogen turns graphene into an insulator with a temperature dependence of the conductivity that points towards a variable range hopping mechanism 13 . For electron-doped (n-doped) graphene on SiC, small H amounts yield a shrinkage of the Fermi surface and a metal to insulator transition (MIT) has been observed with a combined transport and ARPES study 14 . For pristine quasi-freestanding graphene, the opening of a bandgap has been reported upon hydrogenation 7,15 .…”
Section: Introductionmentioning
confidence: 99%